2019
DOI: 10.1253/circj.cj-18-0995
|View full text |Cite
|
Sign up to set email alerts
|

Admission Heart Rate Is a Determinant of Effectiveness of Beta-Blockers in Acute Myocardial Infarction Patients

Abstract: advances in the management of AMI, such as reperfusion therapy, and the use of statins, and angiotensin-converting enzyme inhibitors, have dramatically improved the clinical outcomes of AMI patients. Many observational studies of long-term β-blocker therapy for current AMI patients have B eta-blockers are recommended for long-term management of patients with acute myocardial infarction (AMI), 1-4 but many of the studies that established the effectiveness of β-blockers for AMI patients were conducted several de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As an independent risk factor of cardiovascular diseases, the increase of resting heart rate is positively associated with the mortality of cardiovascular events from AMI (18,19), which leads to the increase of myocardial oxygen consumption amount, the decrease in coronary artery perfusion, causes myocardial ischemia, an increase in the number of necrotic myocardial cells and the reduction of myocardial compliance, which could further cause the heart myocardial remodeling and cardiac function failure (20). Therefore, active clinical control of the resting heart rate has become one of the most important methods for treating AMI (21). Although β-blockers are clinically used to slow down the heart rate, effects such as negative conduction, negative muscle strength, and lower blood pressure, and side effects and contraindications all require consideration with the clinical application of these drugs (22), which limits its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…As an independent risk factor of cardiovascular diseases, the increase of resting heart rate is positively associated with the mortality of cardiovascular events from AMI (18,19), which leads to the increase of myocardial oxygen consumption amount, the decrease in coronary artery perfusion, causes myocardial ischemia, an increase in the number of necrotic myocardial cells and the reduction of myocardial compliance, which could further cause the heart myocardial remodeling and cardiac function failure (20). Therefore, active clinical control of the resting heart rate has become one of the most important methods for treating AMI (21). Although β-blockers are clinically used to slow down the heart rate, effects such as negative conduction, negative muscle strength, and lower blood pressure, and side effects and contraindications all require consideration with the clinical application of these drugs (22), which limits its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 6 conducted a study that revealed the potential of esmolol in attenuating lung injury and inflammation in rats with severe acute pancreatitis. Notably, compelling evidence suggests that effective control of a rapid heart rate can significantly improve the prognosis of patients afflicted with liver cirrhosis 16 , sepsis 12 , Marfan syndrome 17 , congestive heart failure 18 , and uncontrolled hypertension 19 . Given the potential clinical significance of heart rate management, our study contributes to the existing knowledge by establishing a research foundation for exploring the impact of heart rate control specifically in the context of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…17) Admission HR was a determinant of effectiveness of beta-blockers for patients with AMI, and HR at discharge independently predicted long-term aortic outcomes in surgically treated patients with type A AAD. 18,19) However, the relationship between HR at admission and clinical outcomes in patients with AAD is unknown.…”
Section: Discussionmentioning
confidence: 99%